2017
DOI: 10.1186/s40101-017-0147-5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation effects in static postural control by providing simultaneous visual feedback of center of pressure and center of gravity

Abstract: BackgroundThe benefit of visual feedback of the center of pressure (COP) on quiet standing is still debatable. This study aimed to investigate the adaptation effects of visual feedback training using both the COP and center of gravity (COG) during quiet standing.MethodsThirty-four healthy young adults were divided into three groups randomly (COP + COG, COP, and control groups). A force plate was used to calculate the coordinates of the COP in the anteroposterior (COPAP) and mediolateral (COPML) directions. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
2
22
0
1
Order By: Relevance
“…Despite the lack of an interaction effect, the effect size analysis evidenced a greater impact of real-time visual feedback in almost all variables. According to the present results, previous findings showed that VFT was effective in enhancing postural control [ 18 , 34 , 35 ]. Furthermore, a recent study showed significant improvements in postural sway following one session of real-time visual feedback practice in ~16 year old young karate athletes [ 19 ].…”
Section: Discussionsupporting
confidence: 81%
“…Despite the lack of an interaction effect, the effect size analysis evidenced a greater impact of real-time visual feedback in almost all variables. According to the present results, previous findings showed that VFT was effective in enhancing postural control [ 18 , 34 , 35 ]. Furthermore, a recent study showed significant improvements in postural sway following one session of real-time visual feedback practice in ~16 year old young karate athletes [ 19 ].…”
Section: Discussionsupporting
confidence: 81%
“…However, in these studies subjects were instructed to focus on the movement around the ankle joint rather than the movement of the CoP, which might account for the inconsistent findings. It appears that the CoP movements are not simply the representations of the CoM but might also fulfill other sensory acquisition functions (Murnaghan et al, 2011 ; Takeda et al, 2017 ). Our results indicate that the healthy cohort performed standing with near-minimum variability, with the remaining variability probably resulting from the neuromuscular noise (Singh et al, 2012 ), and therefore do not support the hypothesis of flexible motor variability control by the HSMS.…”
Section: Discussionmentioning
confidence: 99%
“…It comprised of balance training for 30 min each (static standing for 30 s) at intervals of 1-2 days. In OLS, participants were instructed to stand on their dominant leg, while the non-supported leg was flexed at the knee with the plantar surface of the foot stabilized on the knee of the supporting leg [15]. In TS, the participants ' feet (on a line, heel-toe position) were placed on the center of the force plate [16].…”
Section: Methodsmentioning
confidence: 99%